BOOK REVIEW OF SUSAN WICKS DRIVING MY FATHER - Putri, Vininda (LANTERN (Journal on English Language, Culture and Literature), 2015)
Love is an essential thing in human life. Everybody needs to love and be loved. There are kinds of love such as love between parents and their children, two lovers, and even human and God. However, people have a different way of interpreting and have an own definition about love. Most people assume that when they love someone, the loving one also must repay what they have been given to them.